Tinjauan Yuridis Faktor Kekerasan Dalam Rumah Tangga Dalam Gugatan Pada Perkara Cerai Gugat Tahun 2024 Di Pengadilan Agama Teluk Kuantan: Penelitian - Aprinelita; Afrinald Rizhan; Muhammad Iqbal; Rismahayani; Ita Iryanti; Shilvirichiyanti; Adilla Sandia Fitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Marriage is an important event in human life because marriage concerns the personal affairs of the bride and groom but also concerns family and community affairs in fulfilling their life needs. In marriage or household, sometimes there are disputes between husband and wife that can lead to a desire for divorce, the cause of disputes can be caused by several factors such as economic, infidelity, domestic violence and others. To resolve marital problems, the State provides a means or place to resolve them, in this case regarding the resolution of problems related to marriage, it is done in court, especially for those who are Muslim, it is done in a religious court. One of the factors that causes problems in marriage is domestic violence (KDRT). If the wife experiences domestic violence, the wife can file for divorce in the religious court. When filing a lawsuit for divorce, a lawsuit for divorce is filed by submitting a lawsuit in the religious court by including a lawsuit containing domestic violence in the divorce lawsuit in the Posita and Petitum. Contested divorce is one of the legal cases in religious courts, where in the case of marriage, contested divorce is a case filed by the wife to sue her husband for divorce based on various factors that the wife has experienced in her home.